Simulation of air flow distribution in a tray dryer by CFD - Misha, Suhaimi; Mat, Sohif; Mohd Rosli, Mohd Afzanizam; Ruslan, Mohd Hafidz; Sopian, Kamaruzzaman; Salleh, Elias @ Ilias (WSEAS Press, 2015)
Application of tray dryer is widely used in agricultural drying because of its simple design and capability to dry products at high volume. However, the greatest drawback of the tray dryer is uneven drying because of poor airflow distribution in the drying chamber. Implementing the proper design of a tray dryer system may eliminate or reduce non-uniformity of drying and increases dryer efficiency. This This study investigates the airflow distribution throughout the drying chamber by using Computational Fluid Dynamics simulation for kenaf core drying. The experimental and simulation data exhibit very good agreement. The drying rate of dried products in each tray was predicted using the validated data. The result shows that, the higher the air velocity, the higher the drying rate of the products. The alternate arrangement of tray position was adopted to ensure that all trays are exposed directly to drying air and to improve airflow distribution throughout the drying chamber. There was a variation of final moisture content for product at different columns. As the distance of product far from the air inlet, the air velocity decreased. However the uniformity of air flow distribution to each level of product at the same column are acceptable.